The Corelation Knowledge Be About Pregnancy Maternal Care (ANC) Towards Antenatal Care Mojoroto Village District Kediri - darmayanti, Rofik; Betristasia Puspitasari (Sean Institute, 2024)
Antenatal care (ANC) is treatment given to mother during pregnancy. Antenatal care is effort together both health officer and pregnant mother, that is consist of check pregnancy and correlation effort to deviation had found.The important of antenatal care to guarantee natural process in order to normally, during pregnancy. The knowleg during pregnant mother is very important because can be influences of pregnancy, that is fetus. The purpose of research is to know the correlation between knowleg be about pregnancy maternal care towards antenatal care. The design of research is used on this research is correlation study, with cross – sectional approach. The population research is all of pregnant mother done on Mojoroto Village Kediri Regency at 37 people.Total sample 30 responden using purposive sampling, Independen variable (Knowledge be abaut pregnancy maternal care) and dependent variable (Antenatal regularly). The collecting data using questionnaire done on 14 - 26 November 2023, then processing data by editing, coding, tabulating, scoring. The result of research got that knowledge be abaut pregnancy maternal care have good criteria is 20 responden (66,6%) and visited antenatal care toward regulare criteria are 19 responden (63,3%). Statistics test Chi Square p value 0,001 < 0,05. It can be concluded that H1 accepted, it means mat the correlation between knowledg be about pregnancy maternal care towards antenatal care. The conclusion in this research that good of knowledge would be caused antenatal care regularly, poor of knowledge would be show that poor regularly on antenatal care. So that, needed lead knowledge maximally to get antenatal care regularly in order to pregnancy of mother to be normal.